GLOBAL WARMING AND CLIMATE CHANGE: NEXT GENERATION BIOFUELS AND ROLE OF BIOTECHNOLOGY: Life Science - Botany - SAINI, SHEETAL; SHARMA, MEGHENDRA; KUMAR , ASHWANI (International Journal of Life Science and Pharma Research, 2018)
Global warming and resultant climate change poses threat to the human population, agriculture, flora and fauna. Increase in the atmospheric concentrations of green house gases results in warming of earth temperature. This can have adverse effect on agricultural crops, result in faster melting of glaciers and rising sea levels, excessive rains, floods and droughts. CO2 is major green house gas and fossil fuels contribute major share of CO2 emissions. Within a short span of 200 years the atmospheric CO2 concentrations have increased by about 40 percent with more than half the increase occurring since 1970. During last 100 years global mean temperature has increased by about 0.8 o C. Most of the plants have a capacity of absorbing Carbon di Oxide and store it in themselves for long time in form of woody biomass. The use of biomass for energy and industry allows significant quantity of hydrocarbons to be consumed without increasing the CO2. This makes a positive contribution to the Greenhouse effect and offers solutions to the problems of "global change". Biotechnology plays an important role in developing synthetic organisms for better conversion of lignocellulosic biomass into biofuels. Some of the recent findings shall be reviewed.